2018
DOI: 10.1016/j.bar.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management using classification shifting of revenues

Abstract: This paper examines a novel form of classification shifting as an earnings management tool using a sample of 12,804 UK listed firm-year observations for the 1995-2014 period. It proposes a new approach to classification shifting whereby firms have scope to misclassify revenues from non-operating activities as operating revenues. The results establish that firms engage in classification shifting of non-operating revenues to inflate operating revenues.They indicate that firms in the period following mandatory IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
102
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(119 citation statements)
references
References 49 publications
8
102
1
3
Order By: Relevance
“…Some previous studies about the effect of IFRS adoption on earnings management resulted in various outcomes. Some researchers argued that IFRS adoption reduce earnings management (Barth, Landsman, & Lang, 2008;Iatridis & Sotiris, 2010;Zéghal, Chtourou, & Sellami, 2011;Dimitropoulos et al, 2013;Pelucio-Grecco et al, 2014;Baig & Khan, 2016), while other studies suggested an increase in earnings management (Callao & Jarne, 2010;Capkun, Collins, & Jeanjean, 2016;Oz & Yelkenci, 2018;Malikov, Manson, & Coakley, 2018), even some studies indicate no effect of earnings management (Jeanjen & Stolowy 2008;Wang & Campbell 2012;Doukakis, 2014;Brice, Ali, & Maher, 2015;Trimble, 2018). Most of the studies had used accrual earnings management (AEM).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies about the effect of IFRS adoption on earnings management resulted in various outcomes. Some researchers argued that IFRS adoption reduce earnings management (Barth, Landsman, & Lang, 2008;Iatridis & Sotiris, 2010;Zéghal, Chtourou, & Sellami, 2011;Dimitropoulos et al, 2013;Pelucio-Grecco et al, 2014;Baig & Khan, 2016), while other studies suggested an increase in earnings management (Callao & Jarne, 2010;Capkun, Collins, & Jeanjean, 2016;Oz & Yelkenci, 2018;Malikov, Manson, & Coakley, 2018), even some studies indicate no effect of earnings management (Jeanjen & Stolowy 2008;Wang & Campbell 2012;Doukakis, 2014;Brice, Ali, & Maher, 2015;Trimble, 2018). Most of the studies had used accrual earnings management (AEM).…”
Section: Introductionmentioning
confidence: 99%
“…
This research aims to examine the effect of the company's management practicing earning management methods through intentional misclassify of revenue and expense items in the income statement(classification shifting) on the operating income Quality by applying to a sample of corporation companies registered on the Egyptian Stock Exchange during the period from 2012 to 2018, and to achieve study goal, The researcher depend on two models, one of which links the intentional misclassifying of expenses items in the income statement and its implication on the operating income quality. The researcher adopted the proposed model in a study (McVay, 2006), which is one of the most common models in accounting literature in the field of intentional misclassifying of expenses items in the income statement, and it is considered the first study that presented an applied evidence to reclassifying the of expenses items in the income statement in the context of American companies, and the second model link between the intentional misclassifying of revenue items in the income statement and its implications on the operational income quality, and the researcher adopted the proposed model in a study (Malikov, et al, 2018).The importance of the study is that it provides an imperial evidence from the Egyptian business environment, as the researcher relied on companies operating in the real estate sector, for sample of (19) companies, for the period from 2012 to 2018 (133 observations), and the researcher concluded that there is evidence from the field of the environment Egyptian business on these companies' practices of earning management by managing the items of operating expenses and including them in non-operating expenses as well as managing the presentation of non-operating revenue items and their inclusion in operating revenues with the aim of inflating operating income, which adversely affected ‫محمود‬ ‫العيسوي‬ ‫الحميد‬ ‫عبد‬ ‫د/‬ .............. ‫بنود‬ ‫عرض‬ ‫إدارة‬ ‫خالل‬ ‫من‬ ‫األرباح‬ ‫إدارة‬ ‫ممارسات‬ ‫أثر‬ 3 the quality of operating income. The researcher believes that this study is one of the first studies at the level of the Arab world -within the limits of the researcher's knowledge -that dealt with the relationship between intentional misclassifying of income statement items and operating income quality.The results of this study have implications for the professional bodies responsible for setting accounting standards as well as supervisory and oversight bodies for Egyptian companies, whereby artificially inflating operational income affects investment decisions and thus resource allocation decisions.
…”
mentioning
confidence: 99%
“…This research aims to examine the effect of the company's management practicing earning management methods through intentional misclassify of revenue and expense items in the income statement(classification shifting) on the operating income Quality by applying to a sample of corporation companies registered on the Egyptian Stock Exchange during the period from 2012 to 2018, and to achieve study goal, The researcher depend on two models, one of which links the intentional misclassifying of expenses items in the income statement and its implication on the operating income quality. The researcher adopted the proposed model in a study (McVay, 2006), which is one of the most common models in accounting literature in the field of intentional misclassifying of expenses items in the income statement, and it is considered the first study that presented an applied evidence to reclassifying the of expenses items in the income statement in the context of American companies, and the second model link between the intentional misclassifying of revenue items in the income statement and its implications on the operational income quality, and the researcher adopted the proposed model in a study (Malikov, et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations